Treated post-acute sequelae after COVID-19 in a German matched cohort study using routine data from 230,256 adults - Müller, Doreen; Stengel, Sandra; Roesler, Martin; Schillinger, Gerhard; Dräther, Hendrik; Günster, Christian; Tillmanns, Hanna; Erhart, Michael; Szecsenyi, Joachim; Merle, Uta (Frontiers in Epidemiology, 2023)
Background The aim of this study was to evaluate treated post-acute sequelae after inpatient or outpatient management of acute COVID-19. Method 50 outcome variables at disease, symptom and treatment levels (14 main categories and 36 sub-categories; new diagnoses) were defined from routine data and logistic regression was carried out for patients tested positive in a PCR test in March/April 2020 for SARS-CoV-2, with an outpatient and inpatient, risk-adjusted (age, administrative region, 1:5 propensity score matching), contemporaneous non-COVID-19 control group (CG). Results The mortality rate in the outpatient (COV-OUT) (n=32,378) and inpatient (COV-IN) (n=5,998) patients treated for COVID-19 is higher compared to the control group with odds ratio (OR) 1.5 (1.3-1.6) and/or 1.7 (1.5-1.8) respectively. At least one outcome variable was seen more frequently in COV-OUT and COV-IN compared to the CG (OR 1.4 (1.4–1.4); OR 2.5 (2.4–2.6)). 42 out of 50 (COV-IN) and 37 out of 50 (COV-OUT) outcome variables showed increased ORs. COV-OUT: The main category loss of taste and smell (5.8; 5.1-6.6) and sub-categories interstitial respiratory diseases (2.8; 2.0-4.1) and breathing disorders (3.2; 2.2-4.7) showed the highest ORs. COV-IN: The sub-categories interstitial respiratory diseases (12.2; 8.5-17.5), oxygen therapy (8.1; 6.4-10.2) and pulmonary embolism/anticoagulation (5.9; 4.4-7.9) were the most pronounced. Conclusion Following a SARS-CoV-2 infection (wild type), 25.5 (COV-IN) respectively 8.4 (COV-OUT) percentage points more subjects showed at least one new diagnosis, symptom or treatment compared to the CG. Because the symptoms and diagnoses are so varied, interdisciplinary and interprofessional cooperation among those providing management is necessary.